2005
DOI: 10.1007/s00405-004-0889-7
|View full text |Cite
|
Sign up to set email alerts
|

Deep neck infection due to Lactococcus lactis cremoris: a case report

Abstract: This report describes the first case of deep neck infection resulting from Lactococcus lactis subsp. cremoris. The case is associated with the consumption of unpasteurized milk and occurred in a patient with a buccal mucosa tumor. Anti-infective therapy with ceftriaxone and metronidazole resulted in complete resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 11 publications
0
22
2
Order By: Relevance
“…In some cases, the ingestion of unpasteurized milk, sour cream, or yogurt was recognized [5,6,9,[11][12][13]. Our patient and other previously reported cases [2,3,10,14], however, had no history of ingestion of unpasteurized milk, sour cream, nor yogurt.…”
contrasting
confidence: 49%
See 1 more Smart Citation
“…In some cases, the ingestion of unpasteurized milk, sour cream, or yogurt was recognized [5,6,9,[11][12][13]. Our patient and other previously reported cases [2,3,10,14], however, had no history of ingestion of unpasteurized milk, sour cream, nor yogurt.…”
contrasting
confidence: 49%
“…Only a few cases of human infection due to L. lactis have been reported in the English literature, namely, a liver abscess in an elderly patient, cerebellar abscess, septicemia in a patient with chronic lymphocytic leukemia, septic arthritis, necrotizing pneumonitis, peritonitis in an automated peritoneal dialysis patient, and deep neck infection [2,3,[5][6][7][8][9]. Only three cases of infective endocarditis secondary to L. lactis subsp.…”
mentioning
confidence: 95%
“…Only a few adult cases have been reported in the literature including septicemia, endocarditis, pneumonitis, arthritis, liver abscess, and deep neck infection [2,[7][8][9][10]. Only one case of central nervous system infection in adult caused by L. lactis subsp.…”
Section: Discussionmentioning
confidence: 95%
“…Penicillin or third-generation cephalosporin is commonly preferred [1,6,9]. In addition, it was reported that L. lactis might be sensitive to antibacterials such as ß-lactams, macrolides, aminoglycosides, and vancomycin [1,2,12,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation